Effect of different cavity conditioners on microleakage of glass ionomer cement with a high viscosity in primary teeth - Romina Mazaheri; Leila Pishevar; Ava Vali Shichani; Sanas Geravandi (Wolters Kluwer Medknow Publications, 2015)
Background: Glass ionomer cement is a common material used in pediatric dentistry. The aim of this study was to evaluate the microleakage of high-viscosity glass ionomer restorations in deciduous teeth after conditioning with four different conditioners. Materials and Methods: Fifty intact primary canines were collected. Standard Class V cavities (2 mm × 1.5 mm × 3 mm) were prepared by one operator on all buccal tooth surfaces, including both enamel and dentin. The samples were divided into five groups with different conditioners (no conditioner, 20% acrylic acid, 35% phosphoric acid, 12% citric acid, and 17% ethylenediaminetetraacetic acid [EDTA]). Two-way - ANOVA, Kruskal-Wallis and Mann-Whitney tests were used to compare the means of microleakage between the five groups. The significance level was set at P < 0.05. Results: There was no significant difference between the means of microleakage in incisal (enamel) and gingival (dentin) margins (P = 0.34). Furthermore, there was no significant difference between the means of microleakage in enamel and dentin margins (P = 0.4). There was a significant difference between the means of microleakage in different groups (P = 0.03). Conclusion: Within the limitations of this study, it is suggested that 20% acrylic acid and 17% EDTA be used for cavity conditioning which can result in better chemical and micromechanical adhesion.